Improving drought tolerance in rice: Ensuring food security through multi‐dimensional approaches. Issue 2 (27th October 2020) - Khan, M. Iqbal R.; Palakolanu, Sudhakar R.; Chopra, Priyanka; Rajurkar, Ashish B.; Gupta, Ravi; Iqbal, Noushina; Maheshwari, Chirag
Abstract: Drought has been highly prevalent around the world especially in Sub‐Saharan Africa and South‐East Asian countries. Consistent climatic instabilities and unpredictable rainfall patterns are further worsening the situation. Rice is a C3 staple cereal and an important food crop for the majority of the world's population and drought stress is one of the major growth retarding threats for rice that slashes down grain quality and yield. Drought deteriorates rice productivity and induces various acclimation responses that aids in stress mitigation. However, the complexity of traits associated with drought tolerance has made the understanding of drought stress‐induced responses in rice a challenging process. An integrative understanding based on physiological adaptations, omics, transgenic and molecular breeding approaches successively backed up to developing drought stress‐tolerant rice. The review represents a step forward to develop drought‐resilient rice plants by exploiting the knowledge that collaborates with omics‐based developments with integrative efforts to ensure the compilation of all the possible strategies undertaken to develop drought stress‐tolerant rice.